Status of Tomato Yellow Leaf Curl Virus in Tomato in the Western Hills of Nepal - Ghimire, Sita R; Subedi, Phul Prasad; Green, Sylvia K (Nepal Agriculture Research Journal, 2011)
Tomato cultivation in rainy season is being endangered and is becoming less profitable because of tomato yellow leaf curl virus (TYLCV) infection. Studies were conducted at Agriculture Research Station, Lumle to assess the incidence of TYLCV and associated yield losses in various commercial tomato growing pockets of the western hills during the period of 1995 and 1997. The studies revealed a high incidence of the disease in most tomato growing pockets and yield losses of 40% or even higher have been reported in some areas like Risingpatan, Tanahun and Kudule, of western hills of Nepal. Laboratory analysis of the diseased samples by Asian Vegetable Research and Development Center revealed the presence of three different strains of TYLCV: Banglore I, Banglore II and Sri Lanka in the western hills. The TYLCV vector, whitefly (Bemisia tabaci Gen.), was found active throughout the crop growing period in some commercial tomato growing pockets. Therefore, research on the development of effective TYLCV management technology is needed to sustain rainy season tomato cultivation in the western hills of Nepal. Key words: Bemisia tabaci; Lycopersicon esculentum; Tomato; Yellow leaf curl virus; Whitefly DOI: http://dx.doi.org/10.3126/narj.v4i0.4856 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 1-4 Uploaded date: 8 June, 2011